+0  
 
0
75
1
avatar

limx→∞ 2x^3 + x − 6/ (3x − 1)2(x + 3) =

limx→∞ x^2 + x − 6 /(x + 3)(x 2 − 7) =

thanks!

 Apr 1, 2021

Best Answer 

 #1
avatar+594 
+1

For the first one, $\deg(denom)<\deg(num)$ so it goes to infinity

For the second one, $\deg(denom)>\deg(num)$ so it goes to zero.

 Apr 1, 2021
 #1
avatar+594 
+1
Best Answer

For the first one, $\deg(denom)<\deg(num)$ so it goes to infinity

For the second one, $\deg(denom)>\deg(num)$ so it goes to zero.

thedudemanguyperson Apr 1, 2021

17 Online Users

avatar